Waterlogging Simulation and Drainage Effect Assessment of Deep Tunnel Engineering in a Coastal City Based on MIKE - TAN Yin; TU Xinjun; YU Honggang; LIN Kairong; LIU Meixian; MA Ke (Renmin Zhujiang)
Under the influence of extreme hydrometeorological conditions such as rainstorms and storm surges, the waterlogging issue in coastal areas with rapid urbanization has become increasingly prominent. Taking the western region of Shenzhen City in the Guangdong-Hong Kong-Macao Greater Bay Area as the study area, this paper couples a one-dimensional river flood model, a pipeline drainage model, and a two-dimensional overland flow model to simulate urban waterlogging processes under extreme precipitation and typical storm surge. The waterlogging risk classification is conducted and the drainage effect of deep tunnel engineering is evaluated. The results show that the formation processes and inundation characteristics of urban waterlogging can be better simulated using the combination of multiple MIKE model tools, and changes among waterlogging risk levels can be more clearly presented by the probability matrix method. Under extreme hydrometeorological conditions, the waterlogging inundation in coastal cities exhibits rapid increase and slow decrease. For designed 2-hour extreme precipitation with 50-year and 100-year return periods, the waterlogging risk range accounts for 4.24 km2 and 5.04 km2, respectively. Specifically, the relative area proportions among risk levels 1 to 4 are 0.9:37.5:28.5:33.0 and 4.0:33.7:26.8:35.5, respectively; the inundation and waterlogging risk ranges with deep tunnel engineering decrease by 17.0% and 13.4%, and by 28.8% and 30.2% respectively; the inundation duration of typical waterlogging-prone regions is shortened by 60.0%~80.8%. The significant decrease in the risk level of waterlogging in most areas demonstrates that the drainage effect of deep tunnel engineering is significantly improved.